Religion and Morality: The study of The Religious Phenomenology Study of Gays Community - Kahmad, Dadang; Herlina, Lina; Suryahim, Iim; Amin, Hadi Nur (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to give a picture to the public about gays in terms of religion and morality, so they can find out whether gays can carry out their religion and have morals in accordance with the religion in which they profess. The research method used is a qualification in order to describe all the behavior of gays in everyday life. Findings about the moral and religious beliefs of gay people are still questioned by many people, and almost the community judges Gay people are not moral and disobedient to their religion, but in the midst of many gay people still perform prayers, zakat, umrah and even Hajj. The conclusions of this study provide a description that what happens to the gay religious phenomenon will be in the spotlight because not every gay person has no morals and does not obey religion. This research is basically an attempt by the writer to study and analyze the problem of the phenomenon of homosexuality and religious practices of homosexuals, especially gays, in the context of religious relations and morality.